Study on the binding behavior and functional properties of soybean protein isolate and β-carotene - Zhang, Yating; Zhao, Wenqi; Xing, Zhuqing; Zhu, Beibei; Hou, Ruiyang; Zhang, Junxi; Li, Taoran; Zhang, Zifan; Wang, Hongwu; Li, Zheng (Frontiers in Nutrition, 2022)
This study focused on the non-covalent interaction between SPI and β-carotene. The conformational changes of SPI with β-carotene in varying proportions (BC/SPI: 2%, 4%, 6%, 8%, 10%) were investigated by multi-spectroscopy and molecular docking. Results showed that the quenching mode is static quenching and binding affinity increased with temperature. The stoichiometry was 1:1, indicating there was only one binding site in SPI. The binding was based on entropy and primarily driven by hydrophobic interactions and its binding constant was in the order of 104 L∙mol-1. The addition of the β-carotene affected the secondary structure of SPI resulting in an increase in α-Helix and decrease in random coil and β-turn content, indicating protein aggregated and hydrophobic interactions occurred. SDS-PAGE verified that no new larger molecular weight substance was formed and no covalent interaction existed. Molecular docking corroborated that electrostatic and hydrophobic interactions were both involved in the formation of complexes, where hydrophobic interaction was the dominant one. Moreover, β-carotene improved DPPH radical scavenging activity, foaming capacity and emulsifying stability of SPI. These findings provide useful information about the interaction mechanism of SPI and β-carotene, which contributes to the further development and application of SPI products rich in β-carotene in food industry.